A austeridade fiscal e o financiamento do Sistema Único de Saúde na Região Nordeste - Galhardo, Talita Cordeiro (2023)
The Unified Health System (SUS) is the result of the articulation and struggle of the Brazilian population to make access to universal public health a right. However, its history is marked by the problem of funding, which mainly affects states and municipalities in the North and Northeast regions, rural areas, territories of native and traditional peoples, low-income communities and small towns. There are several reasons for the underfunding of the SUS, including the idea and practice of fiscal austerity, understood in this paper not as a technical issue, but as a worldview, a value that has been reinforced since the 1970s with neoliberalism. The main idea behind this economic orientation is that of a minimal state, in which the values of private initiative are valued and state intervention in the economic and social spheres is limited, as opposed to the welfare state. In Brazil, austerity was disseminated mainly from the 1990s onwards, with the neoliberal principles of the Washington Consensus (1989). Even with the 1988 Federal Constitution (CF/88), which prioritised the transfer of resources to the states and municipalities for social policies, these transfers were affected by various rules on the untying of revenue, and only in 2012 the Complementary Law regulating minimum amounts for public health was sanctioned. Austerity in public health would be deepened by Constitutional Amendment 95/2016. Thus, this work analyses whether fiscal austerity is more detrimental to the Northeast region than to other Brazilian regions and whether austerity hinders the right to the provision of public health policies and the relationship between SUS underfunding and access to public health services in the Northeast region using the qualitative method, exploratory research and descriptive research. The issue behind the underfunding of the SUS is the small contribution compared to nominal GDP, which currently stands at 3.8 per cent. Universalisation and comprehensiveness require approximately 10% of GDP for public health, as is the case in other countries with a universal system. Furthermore, there is a reduction in health resources in the face of a demographic transition. Since the North and Northeast regions presente inferior epidemiological conditions than the rest of the country and are more in need of the SUS, a better distribution of resources and less austerity are needed to achieve their development. Given that the North and Northeast have unfavourable socioeconomic situation in relation to the other regions, it is considered that the Northeast is more affected by fiscal austerity than the Centre-West, Southeast and South regions, and is similar to the North. Finally, the decision on taxes is a political choice made by society, according to its values and objectives, and the most necessary debate is about the type of State Brazil wants to have, whether it is a State based on social solidarity or on the neoliberal precepts of competition and profit.